“Why would we?” A qualitative study on COVID-19 vaccination decision making among Ukrainian economic female migrants in Poland - Ganczak, Maria; Kalinowski, Pawel; Twardowski, Piotr; Osicka, Dominika A.; Pasek, Oskar; Duda-Duma, Łukasz; Vervoort, Johanna P. M.; Edelstein, Michael; Kowalska, Marta (Frontiers in Public Health, 2024)
Background: Ukraine has one of the lowest COVID-19 vaccination rates in Europe. This may pose a significant epidemiological risk regarding the ongoing pandemic and refugee crisis. Objective of the study was to evaluate determinants of vaccination decision making among Ukrainian female migrants (UFMs). Methods: A qualitative study with 45 UFMs was conducted between December 2021 and January 2022. UFMs, from 2 Polish provinces, differing in age, education and length of stay were invited with the use of the snowball technique. Using a semi-structured topic guide, eight focus groups were conducted in person, recorded and transcribed. Thematic, qualitative analysis was made; key themes which emerged from the data (with the help of the Working Group Determinants of Vaccine Hesitancy Matrix), were related to contextual, individual/group and contextual vaccine/vaccination-specific influences. Results: Mothers were found to be playing a crucial role in children and adolescent COVID-19 vaccine decision-making process. Universal trust in the Polish healthcare system and vaccination procedures, employer requirements and willingness to preserve jobs, desire to get back to normal and social influences were paramount prerequisites to let UFMs make a decision to get vaccinated. However, COVID-19 vaccines also faced backlash among UFMs. Negative experiences with vaccines provided in Ukraine, doubts about the rapid vaccine development, combined with lack of confidence in vaccine safety, specifically regarding child vaccination, might have a bearing on UFMs' decision about declining COVID-19 vaccine while on PAGE \* Arabic \* MERGEFORMAT migration. Discrimination through HCWs during vaccination visits was also reported. Corrupted Ukrainian healthcare system, which facilitates proof forgery regarding vaccination certificates, could act as a negative influencer of UFMs' vaccine decision-making. Conclusions: The results provide the novel information, expressed in economic UFMs' own words. Findings show that influencers of the decision-making process regarding the COVID-19 vaccination are complex and polarized; elements of hesitancy may persist after migration. Any continuation of UFMs' vaccination with COVID-19 vaccine should be subject to designing accessible information to address modifiable demotivators of the vaccine decision-making process identified in this study.